The Influence of Pb Levels in Water on Histopathology of Gills and Kidneys of Hemibagrus nemurus (Valenciennes, 1840) in Siak River, Pekanbaru, Riau - Yusfiati, Yusfiati; Putri, Sri Handayani; Prameswari, Ulan (Universitas Gadjah Mada, 2025)
Waste metals from the Siak River in Indonesia's Riau Province can enter fish organs and change their structure and metabolic functions. This study looks for heavy metal concentrations in the water and structural organ alterations of Hemibagrus nemurus (Valenciennes, 1840). Fish and river water samples were collected at sites 1 (Limah Puluh district) and 2 (Rumbai Pesisir district). The Atomic Absorption Spectrophotometry (AAS) method tests kidney and gill Pb samples. Siak River Pb readings in locations 1 and 2 were 0.113 mg/L and 0.072 mg/L in January 2024 and 0.105 and 0.128 mg/L in October. Gill and kidney Pb were 0.0132 and 0.2726 mg/kg. Fish kidneys were reddish-black at two sites, while gills were bright red at site one and dark red at site two. In all samples, edema, fusion, hyperplasia, telangiectasis, and epithelial lifting indicate fish gill tissue injury. Kidney tissue abnormalities also indicate injury. It is concluded that Pb levels in the Siak River exceeded the permissible limit in 2024, resulting in edema, necrosis, degeneration, and damage to the kidneys and gills of fish. The ecosystem of the river may be harmed by elevated Pb levels in the water, which have also injured fish organs.